Studying the regulatory mechanisms controlling hydrotropism and moisture regulated gene expression in roots. - Low, Darren Yong Yew. (2011)
Roots respond to various environmental stimuli and water in one of them. Under water stress, roots re-orientate and grow towards the side with higher water potential and this is known as hydrotropism. Regulatory molecules such as abscisic acid (ABA) and auxin play a important role in hydrotropism and expression of 9-cis-epoxycarotenoid dioxygenase (NCED) is needed for ABA biosynthesis. Presently, the molecular mechanisms of hydrotropism remain elusive. In this study, we wanted to analyze hydrotropism-deficient Arabidopsis mutants and discover more hydrotropism genes using our present understanding of hydrotropism. Moisture affinity assay and PG1 screening were conducted and many possible mutants of hydrotropism were found. We tried generating 16 more reporter lines for the 16 possible hydrotropism genes found in a prior study but did not manage to generate a single one due to some hiccups in the vector cloning. NCED3p-GFP screening was also done to prepare a NCED3 reporter line for hydrotropism studies. The complementation of the generation of the new reporter lines and the analysis of hydrotropic mutants will definitely help in identifying regulatory molecules and finding links between them. This study has given an taste of what greater discoveries are to come in the scientific research of plant hydrotropism.